Evaluation of the Teaching Performance of Female Health and Physical Education Teachers enrolled in the Optimal Investment Program for Educational Professionals in light of Professional Standards for Saudi Teachers - Al-hazmi, Osama (Journal of Physical Education, 2023)
This study aims to evaluate the teaching performance of female health and physical education teachers enrolled in the program of optimal investment for educational professionals in the light of the professional standards of Saudi teachers issued by the Education and Training Evaluation Commission in Saudi Arabia. To achieve the study’s objectives، the researcher adopted a survey approach to data collection. The number of pedagogical performances in this study is 74 and they were distributed as per the following: performances related to lesson planning (n= 20)، performances related to lesson implementation (n=35)، and performances related to evaluation (n= 19). The study sample (n= 34) were all female teachers. The list of teaching performances was presented to the teachers at the beginning of their enrollment in the optimal investment program، and after completion of the program to measure the overall rate of retention from the program. Four main hypotheses were tested. The first hypothesis was proved give that the Wilcoxon signed-rank test indicated that there were statistically significant differences at 0.05 value in favor of the teachers’ performance at the end of the program with a rate of (21.8%، 17.9%، 21.9%، and 20%) in terms of lesson planning، lesson implementation، evaluation as well as the overall performances. The second hypothesis was also proved. The Kruskal–Wallis one-way analysis of variance test indicated that there are differences in terms of teaching experience in favor of teachers with less than 10 years of experience. The third hypothesis was disproved. The Kruskal–Wallis one-way analysis of variance test indicated that the third hypothesis of the variable of specialization (Islamic studies، Arabic language، and social studies) was not proved. While the Mann Whitney test also indicated that the fourth hypothesis of the variable of graduate studies (postgraduate studies and Bachelor’s) was not proved. Of the recommendations of the study is the continuation of the provision of the optimal investment program for teaching professionals in Saudi Arabia، to review the plans and study programs in preparing physical education teachers، and to add new courses for teachers that equip them with teaching performances that are in line with today’s developments.